KONSEP IJBAR DALAM PERIKAHAN TENTANG KESETARAAN GENDER BERDASARKAN PERSPEKTIF FIQH KONTEMPORER: Kesetaraan Gender - Nerisma, Nerisma Eka Putri (Musawa: Journal for Gender Studies, 2024)
In Islamic law, the right of ijbar is the progressive right of guardian to choose partner for woman in a marriage. The right of ijbar is often misused by guardians to force women under their guardianship to marry the man of their choice without consent, so that women's freedom in choosing a partner is often in conflict with the right of ijbar. The author is interested in studying the concept of ijbar rights in the challenge of gender equality, as well as the fatwa of ulama' and the relevance of ijbar rights based on contemporary fiqh perspectives. This research uses a qualitative descriptive approach. The right of ijbar in gender equality is based on the opinion of the Hanafi school of thought, which prohibits marrying a woman except with her permission. Contemporary fatwas on ijbar rights include Yusuf Al-Qhardhawi who states that a father has no right to force his daughter to marry the man of his choice. Syaikh Nizar Bin Shaleh Al-Syu'aibi stated that marriage is a progressive right of a person, so the guardian has no right to force it. Majma' Al-Fiqh Al-Islami stated that the guardian is not allowed to force his daughter to marry without her consent. KUPI's fatwa of November 26, 2022 states that the state and parties related to forced marriage are obliged to take measures to eliminate the harm caused by forced marriage. KH. Sahal Mahfudh does not recognize the right of ijbar when applied to pubescent women who are virgins or widows.